Physical activity as a predictor of activities of daily living in older adults: a longitudinal study in China - Wang, Ling-Ying; Chen, Hong-Xiu; Zhu, Hong; Hu, Zi-Yi; Zhou, Chun-Fen; Hu, Xiu-Ying (Frontiers in Public Health, 2024)
Objective: This study aimed to assess the prevalence of physical activity and its association with the progression of difficulty performing activities of daily living among older adults in China.: A population-based prospective cohort study based on China Family Panel Studies (CFPS) data was conducted in 2018 and 2020. This study used a logistic model to empirically estimate the effects on daily living activities among older adults.Results: A total of 2073 older adults aged 60 years and above were included, 78.0% of whom did not exercise. The logistic regression model revealed several predictive factors for activity of daily living decline among older adults. These included residence status (OR=0.672; 95% CI 0.519 to 0.869; P=0.002), age (OR=0.307; 95% CI 0.169 to 0.557; P<0.001), ethnicity (OR=0.511; 95% CI 0.338 to 0.773; P=0.001), education level (OR=2.180; 95% CI 1.366 to 3.479; P<0.001), job (OR=0.601; 95% CI 0.447 to 0.810; P=0.001), chronic disease (OR=0.769; 95% CI 0.604 to 0.978; P=0.032) and physical activity (less: OR=0.464; 95% CI 0.300 to 0.720; P=0.001; adequate: OR=0.512; 95% CI 0.321 to 0.816; P=0.005).Our findings indicate that insufficient physical activity is particularly acute among the elderly. Physical activity has emerged as a significant predictor of decreased daily living activities among older adults. Our research underscores that less and adequate physical activity can prevent a reduction in daily living activities, in contrast to a lack of exercise. The most effective threshold for daily exercise frequency is a session per day, while the ideal exercise duration is 15 minutes. Additionally, the desired intensity for exercise is characterized by rapid breathing and a noticeable heartbeat, accompanied by slight perspiration. Community nurses play a pivotal role in providing health education on daily exercise to the elderly. It is crucial for nurses in community hospitals to closely monitor the daily exercise habits of the elderly, actively disseminate the benefits of exercise, and enhance their current exercise regimens through effective health education, ultimately improving their quality of life.